The Protection of Indigenous Malay People’s Customary Land Rights in Rempang Againts Land Acquisition for National Strategic Projects: Perlindungan Hak Ulayat Masyarakat Melayu Asli Rempang Terhadap Pengadaan Tanah Untuk Pembangunan Proyek Strategis Nasional - Muhammad Al Rasyed; Ridha Wahyuni (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Indonesia recognizes customary law communities and their communal land rights as part of the national legal system, yet implementation often clashes with development agendas. Specific background: The indigenous Malay community of Rempang, settled since 1834, faces land acquisition for the Rempang Eco-City National Strategic Project, raising legal and socio-cultural disputes over displacement. Knowledge gap: Although constitutional and statutory frameworks acknowledge customary land rights, practical enforcement and administrative recognition remain weak, particularly when confronted with national development priorities. Aims: This study analyzes the legal status of the Rempang Malay community as a customary law community and evaluates the protection of their ulayat land rights in the context of land acquisition for national development. Results: Findings show that the Rempang Malay community fulfills all substantive legal elements of a customary law society, but lacks full administrative recognition, resulting in weak legal standing during land acquisition processes. The project also demonstrates insufficient meaningful participation and inadequate compensation mechanisms for cultural and spiritual losses. Novelty: This research highlights the discrepancy between de facto recognition of indigenous rights and de jure administrative acknowledgment in large-scale development cases. Implications: Strengthening formal recognition, ensuring free, prior, and informed consent, and adjusting compensation schemes are crucial to achieving development aligned with social justice and legal sustainability. Highlights: The Rempang Malay community meets the legal criteria of a customary law society but lacks full administrative recognition. Land acquisition for the Rempang Eco-City project demonstrates weak protection and limited community participation. Strengthening legal recognition and applying fair, culturally aware compensation are essential for equitable development. Keywords: Customary Land Rights, Rempang, Indigenous Community, Legal Protection, Land Acquisition